2009
DOI: 10.1177/1359105308097944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Activity and Spirituality in the Health and Well-being of Older Adults

Abstract: Older adults completed questionnaires of religiosity, spirituality and health, as well as of the potential mediators of healthy behaviors and social support. Church membership related to potential mediators and positive health; given membership, frequency of attendance contributed less to health. Existential well-being was strongly related to all outcome health measures. Regression analyses indicated that spiritual wellbeing and prayer contributed to the prediction of psychological wellbeing, subjective well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 20 publications
10
62
2
1
Order By: Relevance
“…9, No. 9; consistent with the previous studies such as Moltafet et al (2010), Lawler-Row and Elliott (2009), Okulicz-Kozaryn (2009), Saundra and Hughey (2003, Krause (2003), Swinyard, Kau, andPhua (2001), Fabricator, Handle, andFenzel (2000), Myers (2000), Asghari and Ghasemi-Joobneh (2014), Moslehi and Ahmadi (2013), Abdollahoor and Manavipoor (2008), Khodayarifard et al (2007) and Hadianfard (2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9, No. 9; consistent with the previous studies such as Moltafet et al (2010), Lawler-Row and Elliott (2009), Okulicz-Kozaryn (2009), Saundra and Hughey (2003, Krause (2003), Swinyard, Kau, andPhua (2001), Fabricator, Handle, andFenzel (2000), Myers (2000), Asghari and Ghasemi-Joobneh (2014), Moslehi and Ahmadi (2013), Abdollahoor and Manavipoor (2008), Khodayarifard et al (2007) and Hadianfard (2005).…”
Section: Discussionsupporting
confidence: 87%
“…The positive religious attitude leads to life satisfaction and life satisfaction is one of the predictors of mental health (Lelkes, 2006). In this regard, Lawler-Row and Elliott (2009) investigated the role of religion and spirituality on health, satisfaction, and well-being of the old people. The results indicated that spirituality is a significant predictor of the psychological well-being, physical and mental health, as well as depression reduction.…”
Section: Introductionmentioning
confidence: 99%
“…17 Some studies clearly point to a direct association between subjective religiosity (considering oneself religious) and conjugal satisfaction, whereas there is an inversely proportional association with depression, use of alcohol, illegal drugs and smoking. 18,19 In our results, subjective religiosity was not found to be statistically associated with the prevalence of CMD. Subjective religiosity was dichotomized into 'yes' or 'no', and the vast majority of interviewees answered 'yes'.…”
Section: Discussioncontrasting
confidence: 58%
“…Lawler-Row and colleagues have shown that (a) religious activity positively predicts psychological well-being ( Lawler-Row & Elliott, 2009 ); (b) forgiveness uniquely predicts measures of objective health status (e.g., physical symptoms, medications, and sleep quality; Lawler et al, 2005 ) and greater social support ( Lawler-Row & Piferi, 2006 ); and (c) forgiveness partially or fully mediates the religion -health relationship ( Lawler-Row, 2010 ). Thus, forgiveness and SPS are hypothesized to have salient mediating roles in the relationship between REL and VOL (see Figure 1 ).…”
Section: Rel Forgiveness Sps and Well-beingmentioning
confidence: 99%